Assessment of the Quality of Smartphone-Based Applications and Games for Teaching Medical Terminology Using the Mobile Application Rating Scale (MARS) - Seyyedeh Fatemeh Mousavi Baigi; Reyhaneh Norouzi Aval; Masoumeh Sarbaz; Khalil Kimiafar (پیاورد سلامت)
Background and Aim: Proficiency in medical terminology is a basic competency of most medical students, which ensures communication with other healthcare providers. Facing the lack of motivation and involvement of students, applications, and games based on smartphones are considered as a possible educational option. Due to the rapid expansion of these applications, a correct evaluation of their quality is often not provided. This study investigated and evaluated the quality of smartphone applications and games for teaching medical terminology. Materials and Methods: A systematic review was conducted in August 2024, in the official stores of Bazaar and Google Play applications. The two main keywords “medical terminology” and “medical vocabulary” were searched in Persian and English. Two evaluators independently downloaded and evaluated smartphone-based applications and games for teaching medical terminology. The same checklist was used for data extraction. The quality of apps was measured using the Mobile App Rating Scale (MARS). The points of each section, the final score of the retrieved applications, and the mean and standard deviation were obtained. Results: In total, eighteen programs were included in this study, four of which were games. The average quality of the programs was between 2.70 and 4.30 (average 3.80) on a scale from 1 (inadequate) to 5 (excellent). The best scores are in performance (mean: 3.91), followed by information quality (mean: 3.15). Aesthetics (mean: 2.56) and mental quality of the program (mean: 2.58) had the lowest scores. Two applications offered data privacy, and four had privacy statements. The game ‘Dean Vaughn’ and the application ‘MediTerm’ received the highest overall scores. Conclusion: This study provides an analysis and description of smartphone-based applications and games for teaching medical terminology to help students and users choose high-quality applications that suit their needs and tastes, and on the other hand, it provides the possibility of identifying research and operational gaps to strengthen and design more effective and better applications for the developers of these applications. The applications evaluated were generally of good overall quality, particularly in terms of functionality and information. However, some applications need to improve aspects such as aesthetics and subjective quality to increase their impact on users and ensure better security and privacy.